PROJECT APPROACHES TO CREATING TOURIST QUESTS - Ноздріна, Лариса (Socio-economic relations in the digital society, 2019)
The article describes that the tourism sector is an important component of the economy of our country, which nowadays is in conditions of rigid world competition. It is noted that  adaptation of the tourism sector to the requirements of sustainable development requires modern design approaches to the introduction of innovative tourism services at the macro level. The principles of development of the tourist industry of the economy as an external environment for the implementation of projects are analyzed, in particular, the placeof the tourist services in Ukraine and the city of Lviv is determined. It is noted that Lviv is one of the leading cultural centers of Eastern Europe, a city with a high level of infrastructure, service and security, and a city with world-class events. The place of quest projects in the general classification system of tourist projects on the basis of sustainable tourism is determined. The approaches to creation of innovative tourism projects, the products of which are quests, are offered. The tourism web-quest project had been classified according of: 1) technology (Internet technology project); 2) product type (Web-resource), product class (Internet portal); 3) activity (development). It is noted that the design of the Web-quest is integrating: both tourist, and IT at the same time. The tourist quest, which is described in the article is also cultural-oriented (immersion in culture, familiarity with history and architecture) and activity-oriented (gaming), and nature-oriented (adventure and outdoor activities). In addition, tourist quest  projects are also divided of the form (Web quests), the mode (real), and the form of work (group). As a example describes of the Quest «Find Lion»: the concept of a project, the purpose, objectives, target audience and budget of the project, as well. indicators of the success of the project, the mechanisms of its sustainability and the tools for project implementation. The expected results of the project will be: a large number of participants in the quest, an increase in the number of tourists in the city, the enrichment of the city budget, the dissemination of interesting information about the cultural monuments of Lviv.
Keywords: sustainable tourism; travel service; quest; project approach; innovative tourism projects; website